Macrophage inflammatory protein 1 alpha expression by synovial fluid neutrophils in rheumatoid arthritis. Issue 5 (1st May 1999) - Hatano, Yoshimi; Kasama, Tsuyoshi; Iwabuchi, Hideaki; Hanaoka, Ryosuke; Takeuchi, Hiroko T; Jing, Lu; Mori, Yoshiaki; Kobayashi, Kazuo; Negishi, Masao; Ide, Hirotsugu; Adachi, Mitsuru
Abstract : OBJECTIVE: To determine the contribution made by synovial fluid (SF) neutrophils to the augmented expression of macrophage inflammatory protein 1 α (MIP-1α) in rheumatoid arthritis (RA). METHODS: Neutrophils were isolated from samples of SF from RA patients and peripheral blood (PB) samples from RA patients and healthy controls. Cell associated MIP-1α was visualised immunohistochemically, and cell associated MIP-1α as well as MIP-1α secreted into the SF was assayed by ELISA. Steady state expression of MIP-1α mRNA was assessed by reverse transcription polymerase chain reaction (RT-PCR). RESULTS: Freshly isolated SF neutrophils contained significantly higher concentrations of both MIP-1α protein and its transcript than PB neutrophils from either RA patients or healthy controls; incubation in the absence or presence of tumour necrosis factor α for 24 hours resulted in a significant increase in MIP-1α secretion by RA SF neutrophils compared with neutrophils obtained from either normal PB or RA PB; and expression of MIP-1α by SF neutrophils was well correlated with both RA disease activity and SF mononuclear cell (MNC) counts. CONCLUSION: Expression and secretion of MIP-1α by SF neutrophils may be indicative of local and systemic inflammation in RA. Moreover, this C-C chemokine may contribute to the recruitment of MNCs from the bloodstream into synovial joints and tissues.